2016
DOI: 10.1021/acsmedchemlett.6b00471
|View full text |Cite
|
Sign up to set email alerts
|

Development of 4-Heteroarylamino-1′-azaspiro[oxazole-5,3′-bicyclo[2.2.2]octanes] as α7 Nicotinic Receptor Agonists

Abstract: ABSTRACT:We describe the synthesis of quinuclidine-containing spiroimidates and their utility as α7 nicotinic acetylcholine receptor (nAChR) partial agonists. A convergent synthetic route allowed for rapid SAR investigation and provided a diverse set of fused 6,5-heteroaryl analogs. Two potent and selective α7 nAChR partial agonists, (21), were identified. Both agonists improved cognition in a preclinical rodent model of learning and memory. Additionally, 5-HT 3A receptor SAR suggested the presence of a steric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Most recent hERG inhibition experimental data of 30 inhibitors reported in the year 2017 [38,39,40,41] and 2018 [29,42] including malarial compounds tested against hERG from Open Source Malaria (OSM) database [43] was gathered to evaluate the performance of the models (see Supplementary Information Table S2). Compounds with known hERG IC 50 values were selected for further evaluation and predictions of all four models.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most recent hERG inhibition experimental data of 30 inhibitors reported in the year 2017 [38,39,40,41] and 2018 [29,42] including malarial compounds tested against hERG from Open Source Malaria (OSM) database [43] was gathered to evaluate the performance of the models (see Supplementary Information Table S2). Compounds with known hERG IC 50 values were selected for further evaluation and predictions of all four models.…”
Section: Resultsmentioning
confidence: 99%
“…The internal test set contained 20 percent (41 compounds) of the overall dataset generated using diverse subset selection procedure. For the external test set all compounds tested against hERG reported in the years 2017 [38,39,40,41] and 2018 [29,42], and the compounds available at Open Source Malaria (OSM) database [43] test against hERG liability were also included. In the data set various filters were applied to reduce the data size such as drug-likeness of compounds rule of five, molecular weight (between 200 and 700 KD), electrophysiology assay (patch-clamp), absolute activity values (pIC 50 ).…”
Section: Methodsmentioning
confidence: 99%
“…26) were identified as potent and selective α7 nAChR partial agonists. 168 In animal models, these two partial α7 nAChR agonists demonstrated an ability to enhance learning and memory function, to reverse memory and sensory gating deficits and also to reduce anxiety. 168…”
Section: Selective Agonists Of Alpha7 Nicotinic Acetylcholine Receptor (α7 Nachr)mentioning
confidence: 99%
“…In developing compounds with optimum α7 receptor partial agonism properties and high selectivity relative to the 5-HT 3A receptor, we found that the choice of the heteroaryl group was an important factor. Compounds that contained 4-aminopyrimidines substituted in the 6-position with aromatic and heteroaromatic rings, and fused heteroaromatics generally provided this combination of characteristics. …”
mentioning
confidence: 99%
“…Most of the compounds in Figure are characterized by a pharmacophoric model consisting of three elements: (1) a rigid bicyclic amine, which serves as a cationic center at physiological pH, (2) an exocyclic amide, carbamate, or carbonyl biosteric heterocycle serving as a central H-bond acceptor (mimicking the ester carbonyl in ACh), and (3) a lipophilic aromatic or heteroaromatic group. Our extensive SAR efforts identified a novel chemotype which conformed to this pharmacophore, with (1 S ,4 S )-quinuclidine serving as the preferred bicyclic amine and ( R )-aminooxazoline (spiroimidate) as an isostere for the central H-bond acceptor (Figure ). In developing compounds with optimum α7 receptor partial agonism properties and high selectivity relative to the 5-HT 3A receptor, we found that the choice of the heteroaryl group was an important factor.…”
mentioning
confidence: 99%